2018
DOI: 10.2139/ssrn.3271283
|View full text |Cite
|
Sign up to set email alerts
|

Still Living With Mortality: The Longevity Risk Transfer Market After One Decade

Abstract: This paper updates Living with Mortality published in 2006. It describes how the longevity risk transfer market has developed over the intervening period, and, in particular, how insurance-based solutionsbuy-outs, buy-ins and longevity insurancehave triumphed over capital markets solutions that were expected to dominate at the time. Some capital markets solutionslongevity-spread bonds, longevity swaps, q-forwards and tail-risk protectionhave come to market, but the volume of business has been disappointingly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…We interpret our results as one of the possible explanations of the higher degree of internationalization of insurance companies with respect to banks after the adoption of Solvency II. Because of the synthetic possibility to diversify through longevity transfer agreements and longevity swaps, our results also explain the high number of such contracts recently signed in the marketplace and the attention dedicated to the growth of the market capacity (Blake et al, 2018). NOTES 1.…”
Section: Discussionmentioning
confidence: 81%
“…We interpret our results as one of the possible explanations of the higher degree of internationalization of insurance companies with respect to banks after the adoption of Solvency II. Because of the synthetic possibility to diversify through longevity transfer agreements and longevity swaps, our results also explain the high number of such contracts recently signed in the marketplace and the attention dedicated to the growth of the market capacity (Blake et al, 2018). NOTES 1.…”
Section: Discussionmentioning
confidence: 81%
“…At present, the longevity risk transfer market is dominated by longevity swaps (cf. Blake et al, 2019). These contracts can either be customized, that is, tailored to the characteristics of the hedger's book population, or index-based and linked to the reference population.…”
Section: Longevity Swapsmentioning
confidence: 99%
“…In addition to the question of how to model longevity risk, its securitization and the recent development of the global longevity risk transfer market have attracted huge attention among both academics and practitioners. For this emerging market, a great variety of longevity-linked securities, also called longevity hedges or longevity derivatives, have been proposed in the literature, see Blake et al (2019) for an overview. However, the longevity risk transfer market is still in an early state and illiquid and incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Future investigation can introduce other mediating variables based on the survey Analyze, construct a multiple mediation model, explore the explanatory power changes of each mediating variable under different moderating variables, and further open the door to the impact of contract flexibility on organizational quality performance. (2) This study uses the method of bootstrap to analyze and find that there is no mediating effect between organizational decoupling and knowledge distance. A single method cannot comprehensively explain that there is really no interaction between the two, so in the future will use a variety of other methods to analyze.…”
Section: Conclusion and Inspirationmentioning
confidence: 99%
“…For the study of contract flexibility, on the one hand, Chiara and Kokkaew [1] found from the perspective of the first social exchange theory that it was found that enhancing contract flexibility can make risk transfer [2] more efficient and reasonable. With the deepening of study, some scholars found that the flexible clauses in the contract cannot be deleted, and the flexibility of the contract gives a solution [3].…”
Section: Introductionmentioning
confidence: 99%